NOBLE GASES IN UREILITES: COSMOGENIC, RADIOGENIC, AND TRAPPED COMPONENTS - Rai V.K.; Murty S.V.S.; Ott U. (My University, 2003)
Abundances and isotopic compositions of Ne (in bulk samples only), Ar, Kr, and Xe have been investigated in 6 monomict, 3 polymict, and the diamond-free ureilite ALH78019 and their acid-resistant, C-rich residues. Isotopic ratios of Kr and Xe are very uniform and agree with data for ureilites from the literature. The measured ratio 38Ar/36Ar showed large variations due to an experimental artifact. This is shown to be connected to the pressure dependence of the instrumental mass discrimination, which for ureilites with their low abundance of 40Ar is different from that of the usual air standard. This observation necessitates a reassessment for the recently reported 36Ar excesses due to possible decay of extinct 36Cl in the Efremovka meteorite.
Keywords: Ureilites